PENDEKATAN PSIKOLOGIS DALAM MENDAPATKAN KEPERCAYAAN KONSUMEN DARI KEGAGALAN PELAYANAN - WAODE MARATUN SHALEHA; AL ASY ARI ADNAN HAKIM; SELVI DILIYANTI RIZKI (Jurnal Bisnis dan Akuntansi, 2021)
The purpose of this study was to determine the effect of Value Co-cration on Perceived Justice, to determine the effect of Service Recovery on Perceived Justice, to determine the effect of Perceived Justice on Emotions and to determine the effect of Emotions on Repurchase Intentios. The sampling technique in this research is judgmental sample. This research was conducted for three months by distributing questionnaires via google form. The number of samples in this study were 300 respondents. The analytical tool used is SEM (Structural Equation Modeling). The results of this study are Utilitarian Value has a positive effect on Perceived Justice. Hedonic value has a negative effect on perceived justice, Making an Apology has a positive influence on perceived justice, Problem Solving has a positive influence on perceived justice, Being Courteous has a positive influence on perceived justice, Providing an explanation has a positive influence on perceived justice, Prompt Handling has Positive influence on the variable Perceived Justice, Perceived Justice has a negative effect on Negative Emotion, Perceived justice has a positive effect on positive emotions, Negative Emotion has a positive effect on Repurchase Intention and Positive Emotion has a positive effect on Repurchase Intention.